Asked
9 months ago

Viewed
629689 times

**Answer:**

**y = x - 3**

**Step-by-step explanation:**

From the table attached,

Scatter plot given in the graph is correct.

Let the equation of the line passing from a point (x', y') is,

y - y' = m(x - x')

m = slope

Slope of the line passing through two points and is given by,

m =

Therefore, slope of the line passing through the points (11, 8) and (12, 9) will be,

m =

Therefore, equation of the line passing through (11, 8) will be,

y - 8 = 1(x - 11)

y = x - 11 + 8

**y = x - 3**

Enter your username or email to reset your password. You will receive an email with instructions on how to reset your password. If you are experiencing problems resetting your password contact us or send us an email